Evaluasi Pengelolaan Sumber Daya Manusia Teknologi Informasi menggunakan Kerangka Kerja Cobit 5.0 (Studi Kasus: Dinas Komunikasi dan Informatika Kota Batu) - Putri Rizki Utami; Widhy Hayuhardhika Nugraha Putra; Suprapto Suprapto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika Kota Batu especially in the field of information technology and computer management, has problems in managing human resources, namely the lack of Civil Servants (PNS) who master information technology. Therefore, do research with qualitative methods by analyzing the level of capability with COBIT 5 framework on the process EDM04 (ensuring resource optimization) and APO07 (managing human resources). The evaluation was conducted using the method of data collection with data triangulation technique, that observation, interview and assessment with the assessment sheet. After an assessment of the Head of Information Security Encoding Section, Head of Application Development Application Section, and Head of General and Civil Service Subdivision, which is determined based on the RACI chart on COBIT 5, it can be seen that the level achieved by Dinas Komunikasi dan Informatika Kota Batu on process EDM04 is at level 1 and the expected target level is level 2. While on process APO07 has reached level 2 and the expected target level is level 3. There is a GAP of 1 level on process EDM04 and APO07. In order for the organization to achieve the expected target level, the recommendations given refer to the base practices, work products, generic practices, and generic work products based on COBIT 5.